2013
DOI: 10.1089/lap.2012.0404
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Intracorporeal Anastomosis Versus Extracorporeal Anastomosis in Laparoscopic Right Hemicolectomy for Cancer: A Case Control Study

Abstract: There are fewer anastomotic and wound complications in RG patients. Intracorporeal robotic-assisted ileocolic anastomosis allows a faster recovery compared with extracorporeal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 17 publications
5
93
1
1
Order By: Relevance
“…A retrospective review of the Healthcare Cost and Utilization Project NIS by Salman et al [5] demonstrated significantly shorter lengths of stay after robotic surgeries (4.9 days) versus open surgeries (6.1 days) across all surgical subgroups. Refinements in surgical techniques, including use of intracorporeal anastomosis has also shown fewer wound and anastomotic complications and faster recovery [9].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of the Healthcare Cost and Utilization Project NIS by Salman et al [5] demonstrated significantly shorter lengths of stay after robotic surgeries (4.9 days) versus open surgeries (6.1 days) across all surgical subgroups. Refinements in surgical techniques, including use of intracorporeal anastomosis has also shown fewer wound and anastomotic complications and faster recovery [9].…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor regarding utilization of robotics for colectomy revolves around cost. Unfortunately, the ACS-NSQIP database does not provide data on cost but two studies have demonstrated increased per-case hospital costs for robotic colectomy when compared to laparoscopy (22)(23). The cost of the robotic platform at the national level is a complex issue which will also factor into the argument for continued utilization of this technology for colorectal operations.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of 48 robotic right hemicolectomies with intracorporeal anastomosis with 48 laparoscopic right hemicolectomies with extracorporeal anastomosis, Morpurgo et al found that LOS was shorter in the robotic group [16]. Casillas et al also demonstrated shorter LOS in favor of the robotic group for colectomies [17].…”
Section: Discussionmentioning
confidence: 99%